2005
DOI: 10.1097/00001813-200503000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel poliglumex (XYOTAX; CT-2103): an intracellularly targeted taxane

Abstract: Paclitaxel poliglumex (CT-2103; XYOTAX) is an innovative macromolecular taxane designed to increase the therapeutic index of paclitaxel. This large macromolecule conjugate of paclitaxel and poly-L-glutamic acid accumulates in tumor tissues by taking advantage of the enhanced permeability of tumor vasculature and lack of lymphatic drainage. Paclitaxel poliglumex prolongs exposure to active drug and minimizes systemic exposure. Preclinical studies in animal tumor models demonstrate enhanced safety and efficacy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(78 citation statements)
references
References 16 publications
1
77
0
Order By: Relevance
“…A recent report confirmed that monoglutamyl-2′-TXL and diglutamyl-2′-TXL are the major intracellular metabolites of PG-TXL (2). Hydrolysis of these metabolites led to the release of free TXL.…”
Section: Introductionmentioning
confidence: 83%
“…A recent report confirmed that monoglutamyl-2′-TXL and diglutamyl-2′-TXL are the major intracellular metabolites of PG-TXL (2). Hydrolysis of these metabolites led to the release of free TXL.…”
Section: Introductionmentioning
confidence: 83%
“…PG has been used for the delivery of several chemotherapeutic agents. One such conjugate, PG-TXL, has successfully advanced into clinical phase III studies (25). In the current study, 4HPR was conjugated to partially cross-linked PG composed of linear PG of low molecular weight (M n =13,000) by linking them together through hydrolytically labile ester bonds (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…PG is an attractive polymeric drug carrier owing to its biodegradability, biocompatibility, and ability to render waterinsoluble drugs water soluble when the drug molecules are covalently conjugated to the PG carrier (24,25). PG has been used for the delivery of several chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…PGA-based formulations have been developed that have significantly enhanced the efficacy of agents, such as camptothecin and paclitaxel, not only by promoting tumour-specific cytotoxicity but also by improving their solubility in blood following systemic administration [1,10]. For instance, clinical studies on paclitaxel polyglumex, a PGA-paclitaxel conjugate, have demonstrated that this drug formulation is preferentially trapped in the tumour microenvironment allowing the tumour to be exposed to significantly higher chemotherapeutic concentrations than those in off-target tissues [7,9,11].…”
Section: Introductionmentioning
confidence: 99%